PERENCANAAN STRATEGIS TEKNOLOGI INFORMASI PADA PT ABC - Saragih, Hoga; Pangestu, Harta (CommIT (Communication and Information Technology) Journal, 2010)
The aims of the research is to analyze business environment and IS/IT at the company, where the method used are interviews and observation in the company. With Balanced Score Card (BSC) and Critical Success Factor (CSF) tool, the real picture of the business environment could be obtained. Result of analysis of this research is an output in the form of IT division strategy i.e. target application needed to support business, technology and human resource to support the target application. From the resulting analysis, it can be conclude that existing business environment should be supported by target application, technology, and human resource to support business strategy.Keywords: Balance Score Card (BSC), Critical Success Factor (CSF), strategy